2020
DOI: 10.1128/aem.00373-20
|View full text |Cite
|
Sign up to set email alerts
|

Several Metarhizium Species Produce Ergot Alkaloids in a Condition-Specific Manner

Abstract: ABSTRACT Genomic sequence data indicate that certain fungi in the genus Metarhizium have the capacity to produce lysergic acid-derived ergot alkaloids, but accumulation of ergot alkaloids in these fungi has not been demonstrated previously. We assayed several Metarhizium species grown under different conditions for accumulation of ergot alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…diketopipearzine or resorcylic acid lactones). Based on genomic sequence data indicating that certain Metarhizium species have the capacity to produce lysergic acid-derived ergot alkaloids, it was experimentally confirmed that they do, but only during insect colonization and not in plants [ 191 ]. Ergot production by the plant-inhabiting Clavicipitaceae is well documented and famously causes serotonergic overstimulation of the central nervous system in animals [ 192 ].…”
Section: Traits For Being Multitalentedmentioning
confidence: 99%
“…diketopipearzine or resorcylic acid lactones). Based on genomic sequence data indicating that certain Metarhizium species have the capacity to produce lysergic acid-derived ergot alkaloids, it was experimentally confirmed that they do, but only during insect colonization and not in plants [ 191 ]. Ergot production by the plant-inhabiting Clavicipitaceae is well documented and famously causes serotonergic overstimulation of the central nervous system in animals [ 192 ].…”
Section: Traits For Being Multitalentedmentioning
confidence: 99%
“…Metarhizium brunneum for these ergot alkaloids (Leadmon et al, 2020). Those I. tricolor seeds that had been cured of fungus by treatment with fungicide (P-) lacked all ergot alkaloids.…”
Section: Retention Times Mass Spectra and Tandem Mass Spectra Matched What Is Found In The Relatedmentioning
confidence: 99%
“…Fumigaclavine C, the pathway endpoint, appears to be a particularly important virulence factor, as strains of the fungus accumulating earlier pathway intermediates had lower virulence (Panaccione & Arnold, 2017). Another study involving the entomopathogen Metarhizium brunneum, showed that this fungus produces high levels of ergot alkaloids when it infects living waxworm larvae (Leadmon et al, 2020). Perhaps ergot alkaloids are used as a virulence factor by the fungus when causing infection.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
See 2 more Smart Citations